Aunt Rose comes to stay - Mitchelhill, Barbara; Macmillan Education (Oxford : MacMillan Education, 2005)
Macmillan English Explorers have been written specifically for young learners of English. They bring first language teaching methods to reading lessons in first foreign language classrooms.
K-3.
English.
Keywords: Aunt -- Fiction; Family -- Fiction; Reading training, English